Study and comparison of image developments in Persian poetry (from classical to contemporary) - Badizadeh, Mohammad Shah (2021)
In any literary style or period, there are always common factors and contexts between poets and writers that make up the color and public space of that period. One of these contexts are elements and themes that are used in poetic images; Elements such as nature, ordinary and peripheral elements, literary subtleties in image making, etc. are the themes that can lead us to obvious differences between the illustrations of each period in each period and can finally be a basis for evaluation. The artistic and imaginative values and features of each period become and lead us to the important point that the image is a representation of sensory effect in language. This sensory effect also includes: the poet's thoughts, feelings and sensory experiences. The importance of illustration and illustration is such that, in the opinion of many, any change in the illustration of the world also leads to a change in the mechanism of the world. What constitutes the basis of the present research is the study and study of the illustration processes of old and new Persian poetry in two ways, method and subject of the image. The results of the present study show that although the overall image structure of Persian poetry from ancient times to modern times has been based on one principle, but the subject of these images is different in two periods so that the image in ancient poetry is based on "nature and imagination". While the basis of the image in contemporary poetry is "man and society".